2014
DOI: 10.4103/1357-6283.134315
|View full text |Cite
|
Sign up to set email alerts
|

Think global, act local: Medical students contextualize global health education

Abstract: In this exploratory study, we find that following exposure to a global health lecture on the challenges of HIV in the developing world, students possessed more favorable attitudes toward the treatment of marginalized local patient populations, a finding that may be exploited in undergraduate and continuing medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…122 Pass/fail grading systems, complemented by standards-based evaluations, are a step along the continuum to recognizing learners as professionals, enhancing intellectual well-being and preparing medical students for life as enduring learners. 123,124 Further, many studies reported that medical learners have higher satisfaction and greater achievement of knowledge-related outcomes when skills are taught in condensed workshops, ranging from 2 hours, 59 to 5 days, 41 to 2 weeks. 51 More research is needed to understand massed versus dispersed learning to maximize intellectual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…122 Pass/fail grading systems, complemented by standards-based evaluations, are a step along the continuum to recognizing learners as professionals, enhancing intellectual well-being and preparing medical students for life as enduring learners. 123,124 Further, many studies reported that medical learners have higher satisfaction and greater achievement of knowledge-related outcomes when skills are taught in condensed workshops, ranging from 2 hours, 59 to 5 days, 41 to 2 weeks. 51 More research is needed to understand massed versus dispersed learning to maximize intellectual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ibrahim et al conducted a study of medical students’ perspectives following a teaching session on treatment of patients who were HIV-positive. Those students who had attended the session expressed a greater willingness to treat marginalized populations than those who had not [22]. Similarly, in an evaluation of a global health course at Harvard Medical School Nelson et al found that 100% of students evaluated felt that they were better prepared to practice medicine in developing countries than previously [27].…”
Section: Discussionmentioning
confidence: 99%
“…A number of papers consider the student perspective [2, 9, 22], but tend to be aspirational, generally promoting a curriculum that develops competencies aligned to the advocacy physician or humanitarian doctor with little description, evaluation or critical analysis of actual interventions and their impact on the wider student body. A number of post-course evaluations also focus on overseas electives using quantitative tools [9, 13, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Studies have shown that students with training in global health demonstrate an increased cultural awareness, willingness to practice in underserved communities, and a more humanistic approach to medicine than those without this exposure. 4,5,7,8 Thus, global health education can be an important avenue to teach students core competencies of medical education.…”
Section: Introductionmentioning
confidence: 99%